2004
DOI: 10.1144/gsl.sp.2004.233.01.04
|View full text |Cite
|
Sign up to set email alerts
|

A review of natural CO 2 accumulations in Europe as analogues for geological sequestration

Abstract: Natural geological accumulations of carbon dioxide occur widely throughout Europe, often close to population centres. Some of these CO2 deposits leak, whereas others are sealed. Understanding these deposits is critical for selecting and designing underground storage sites for anthropogenic CO2. To provide confidence that the potential risks of geological CO2 storage are understood, geologists are required to predict how CO2 may behave once stored underground. Natural CO2 accumulations provide a unique opportun… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
30
0
4

Year Published

2009
2009
2018
2018

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 46 publications
(35 citation statements)
references
References 37 publications
0
30
0
4
Order By: Relevance
“…Studies investigating CO 2 /brine/rock interactions occurring in natural CO 2 -rich siliciclastic reservoirs showed that the majority of reactions involve dissolution of feldspars and micas, and the precipitation of clays (e.g. illite, kaolinite) and carbonates (Baines and Worden, 2004;May, 2005;Moore et al, 2005;Pearce et al, 2004;Watson et al, 2004). Though CO 2 mineralisation in the form of carbonate minerals is argued to be a major sink for CO 2 , detailed geochemical studies found that carbonate precipitation from CO 2 -rich fluids is rather limited (Gilfillan et al, 2009).…”
Section: Introductionmentioning
confidence: 99%
“…Studies investigating CO 2 /brine/rock interactions occurring in natural CO 2 -rich siliciclastic reservoirs showed that the majority of reactions involve dissolution of feldspars and micas, and the precipitation of clays (e.g. illite, kaolinite) and carbonates (Baines and Worden, 2004;May, 2005;Moore et al, 2005;Pearce et al, 2004;Watson et al, 2004). Though CO 2 mineralisation in the form of carbonate minerals is argued to be a major sink for CO 2 , detailed geochemical studies found that carbonate precipitation from CO 2 -rich fluids is rather limited (Gilfillan et al, 2009).…”
Section: Introductionmentioning
confidence: 99%
“…Without regulations or environmental incentives, however, maximization of the amount of oil produced by a given volume of injected CO 2 is the alternative of choice for industry because the operators receive no income or credit for leaving CO 2 in the reservoir. Like hydrocarbons, CO 2 can be found in natural reservoirs (Pearce et al, 1996 and2004). In addition to economic incentives, the CO 2 needs to be of anthropogenic origin for the CO 2 -EOR to have some positive environmental impact.…”
Section: Introductionmentioning
confidence: 99%
“…Indeed, many natural CO 2 fields have been discovered that are far older than this (e.g. Baines & Worden 2004b;Czernichowski-Lauriol et al 1996a;Pearce et al 1996Pearce et al , 2004Zheng et al 2001). For example, the CO 2 in the natural carbon dioxide field at Pisgah Anticline in Central Mississippi, USA is thought to have originated from thermal metamorphism of Jurassic carbonates by the Jackson Dome igneous intrusion during late Cretaceous times (Studlick et al 1990), which ended some 65 million years ago.…”
Section: The Underground Storage Of Comentioning
confidence: 99%